2021
DOI: 10.3389/fgene.2021.690537
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Analyses of Genome-Wide Association Study to Reveal Significant Risk Genes and Pathways in Neuromyelitis Optica Spectrum Disorder

Abstract: BackgroundNeuromyelitis optica spectrum disorder (NMOSD) is an inflammatory disease of the central nervous system and it is understandable that environmental and genetic factors underlie the etiology of NMOSD. However, the susceptibility genes and associated pathways of NMOSD patients who are AQP4-Ab positive and negative have not been elucidated.MethodsSecondary analysis from a NMOSD Genome-wide association study (GWAS) dataset originally published in 2018 (215 NMOSD cases and 1244 controls) was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…None of the variants we identified overlapped with the variants detected in the re-analysis of the Estrada et al. data ( 47 , 48 ), or of a separate association study on a group of Japanese patients ( 49 ). However, the latter study identified a variant in the gene encoding a voltage gated potassium channel, KCNMA1, as increasing susceptibility to NMOSD ( 49 ).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…None of the variants we identified overlapped with the variants detected in the re-analysis of the Estrada et al. data ( 47 , 48 ), or of a separate association study on a group of Japanese patients ( 49 ). However, the latter study identified a variant in the gene encoding a voltage gated potassium channel, KCNMA1, as increasing susceptibility to NMOSD ( 49 ).…”
Section: Discussionmentioning
confidence: 59%
“…The identification of variants in complement genes, including pathogenic mutations, in the NMOSD patient population supports a role for the complement cascade in the pathogenesis of this disease. None of the variants we identified overlapped with the variants detected in the re-analysis of the Estrada et al data (47,48), or of a separate association study on a group of Japanese patients (49). However, the latter study identified a variant in the gene encoding a voltage gated potassium channel, KCNMA1, as increasing susceptibility to NMOSD (49).…”
Section: Whole Exome Sequencingmentioning
confidence: 77%
See 1 more Smart Citation
“…In summary, the potential molecular mechanisms underlying AQP4-seropositive NMOSD may be related to proteins encoded by the novel genes involved in complement activation, antigen presentation, antibody-dependent cytotoxicity, and immune regulation [ 103 ].…”
Section: Genetic Susceptibility To Nmosdmentioning
confidence: 99%
“…Subsequent astrocyte cytotoxicity caused by inflammatory events, such as granulocyte infiltration or macrophage infiltration [ 436 ], leads to the loss of AQP4 and the astrocyte marker glial fibrillary acidic protein (GFAP) as well as the disruption of the blood–brain barrier (BBB), followed by oligodendrocyte and neuronal cell death. Therefore, SNPs in AQP4 [ 156 ] or T cell marker genes (such as CD58 [ 159 , 162 , 163 , 164 ], CD127 [ 165 ], CD226 [ 166 ], and NECL2 [ 155 ]) and susceptible loci related to complement system (such as CFB [ 149 ] and C4B [ 175 ]) or NK cell markers (such as PRF1 [ 151 ]) can be associated with susceptibility to NMOSD.…”
Section: Channelopathiesmentioning
confidence: 99%